The Role of Migration Research in Promoting Refugee Well-Being in a Post-Pandemic Era. (September 2021) - Kraly, Ellen Percy; Reed, Holly E.; Majmundar, Malay K.; McGrath, Susan; Orrenius, Pia; Silva, Romesh; Ford, Sarah Staveteig
This paper summarizes the presentations and discussions of a virtual stakeholder meeting on Refugee Resettlement in the United States which built on the foundation of the May 2019 workshop represented in this special issue. With support from the Robert Wood Johnson Foundation and the Andrew W. Mellon Foundation and hosted by the Committee on Population (CPOP) of the US National Academies of Sciences, Engineering, and Medicine on Dec 1–2, 2020, 1 the meeting convened migration researchers, representatives of US voluntary resettlement agencies, and other practitioners to consider the role of migration research in informing programs serving refugees and migrants during the COVID-19 pandemic, continuing an emphasis on bringing global learning to those on the ground working with refugees. The goal of CPOP's work in this area has always been to build bridges between communities of research and practice and to create a dialogue for a shared agenda. We present the goals and framework for the 2020 meeting, followed by a summary of each of the four sessions and themes that emerged from these discussions. The paper ends by considering effective ways of amplifying the role of research in refugee policy and programs of refugee resettlement in the United States and how demographers and population researchers might contribute to this goal.